(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Good quality of financial reports enhances stakeholders’ confidence and value of listed business entities. The quality of financial reports has attracted the concern of researchers in accounting literature and that there has been an ongoing issue of corporate report quality concern. The capital market globalisation has heightened the pressure to have a standardised financial reporting language, resulting in the expansion in the use of International Financial Reporting Standards (IFRS). Literature has shown that in Nigeria, listed companies were required to use IFRS since 2012 in order to improve the quality of financial reporting and to become a part of the global economy. Nonetheless, ten years after the adoption, there are still concerns on whether there was a real change in the quality of financial reports. This paper explores how the adoption of IFRS affects the quality of corporate financial reporting in particular, in the qualitative attributes of relevance and faithful representation of fundamental nature among listed consumer goods firms in Nigeria. The survey research design was used with the data to be gathered through questionnaire of 100 persons in the top management of 10 purposely selected companies with a response rate of 88%. The analysis of data was performed based on descriptive and correlation. The results indicate strong, positive, and statistically significant effect of IFRS adoption on relevance (Adj R2 = 0.111, F-stat (2, 97) = 68.343, p < 0.05) and also indicate strong, positive, and statistically significant effect of IFRS adoption on faithful representation (Adj R 2 = 0.166, F-stat (2, 97) = 107.840, p < 0.05). The research also finds out that the adoption of IFRS has a tremendous positive impact on the quality of financial reporting in the consumer goods industry of Nigeria but it depends on the strong management skills, the high level of compliance, and effective institutional and regulatory frameworks. Regulators and corporate management are given recommendations on how to enhance these enablers to ensure a good quality of reporting is maintained.